Meander Motif in Décor of the Old Rus’ Church Masonry - Jolshin, Denis D. (Actual Problems of Theory and History of Art, 2015)
The paper is focused on the use of the meander motif in décor of the Old Rus’ church masonry from 11th to early 13th century. Attention is drawn to compositional peculiarities and the diversity of patterns in meander frieze on church faзades in Kiev (St. Sophia, Dormition and Saint Michael’s Golden Dome Monasteries, and The Saviour Church at Berestovo), Chernigov (Transfiguration and Saint Parascheva Piatnitsa Churches), and Polotsk (The Saviour Church in the Convent of Saint Euphrosyne). Comparing these with the contemporaneous phenomenon in Byzantine and Transcaucasian architecture, the author comes to a conclusion that from the first half of 11th century the simple non-directional П-shaped patterns and more complicated variants characteristic of the Constantinople builders’ style were used in parallel. Meander’s place in the façade composition in all the Old Russian churches was meant to disclose the internal structure of buildings.